Evaluation of Turkish Students selection examination questions for Mathematics 2/Algebra (Penilaian soalan peperiksaan pemilihan pelajar Turki untuk Matematik 2/Aljabar) - Ercan Özdemir; Gürsel Güler; Ramazan Dikici (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study examines the 2006, 2007 and 2008 Students Selection Examination questions (Mathematics 2/Algebra) in terms of level and content. The knowledge and skills necessary to answer these questions correctly were examined using questions administered according to the subject areas. The questions were administered to 627 1st grade students studying in different departments of the Faculty of Education of Atatürk University and Rize University. Their answers were used to calculate the item difficulty index of each question. The questions of each year were applied to the 1st grade university students taking the examination and entering the university in that year. Overall, results indicate that students who scored well in the Student Selection Examination, and succeeded in gaining university entrance, had difficulty answering the questions requiring the collective use of conceptual and operational knowledge.